Identidade docente no projeto político pedagógico do curso de pedagogia da Universidade Estadual de Goiás : relação entre política e currículo - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The object of this work was the identity of (the) pedagogue (o). The delimitation was the identity of pedagogue (the) built by 2009 curriculum Faculty of Education of the State University of Goiás - UEG. With the approval of LDB n. 9.394 / 1996, the discussion on (the) pedagogue (the) escalated because the Faculty of Education was threatened with extinction. Their professional identity was defined only with Resolution CNE / CP n.01 / 2006, which has teaching based on that identity. By Resolution, teaching is presented as a pedagogical work that goes beyond the classroom barriers, and an expanded teaching. In this design, (the) pedagogue (o) is characterized as a teacher, manager and researcher. These characteristics can be applied in school spaces and also no school. The expanded teaching embraces the multi-purpose teaching, discussing the pedagogical work with children, youth and adults at different levels and types of education, which requires the (o) pedagogue (a) a theoretical mastery of all disciplines. The overall objective was to identify and analyze what identity of (the) Educator (o) the Pedagogy course curriculum, 2009 PPC UEG, it is proposed form. The specific objectives were to analyze the theoretical framework regarding the identity of (the) pedagogue (o), that curricula are proposed form; analyze the LDB 9.394 / 96 regarding the identity of (the) pedagogue (o), and his work space; analyze the CNE / CP n. 01, 2006, verifying the identity of which (a) Pedagoga (a), that it intends to form; analyze the identity of (the) pedagogue (the) present in the theses and dissertations in the UFG database, PUC - GO, UNB, Capes and articles in Google, delimiting in the years 2009-2015; analyze the 2009 UEG Pedagogy PPC of the aims, graduate profile and course fundamentals in order to understand what the identity of (the) pedagogue (the) he proposes forming. It was a qualitative research of bibliographic and documentary character, and we make use of readings by authors dealing with the Faculty of Education as Saviani (2008) and Silva (2006), professional identity, as Guimarães (2001), Pimenta and Anastasiou (2005) , curriculum and Goodson (2013) and Pacheco (1996); of expanded teaching and versatile as Vieira (2011) and Silva Cruz (2012); besides reading the LDB n. 9.394 / 96; Reading CNE / CP n. 01, 2006; completion of the literature review; interpretation of Pedagogy PPP UEG 2009. The analysis pointed out some contradictions expressed in the curriculum, which allowed us to state that resume writing of that course, as a constitutive element of the initial formation of the identity of (the) pedagogue (the) intends to form for teaching versatility, but not in all levels and modalities, thus meeting of the legal guidelines.
Keywords: Identidade d(a) pedagoga(o); Políticas educacionais e currículo; Docência ampliada e polivalente; Identity d(a) pedagogue(o); Educational and curriculum policies; Teaching expanded an versatile; CIENCIAS HUMANAS::EDUCACAO